2014
DOI: 10.33073/pjm-2014-012
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Promotion Rhizobacteria in Onion Production

Abstract: The aim of the research was to examine the effect of rhizospheric bacteria Azotobacter chroococcum, Pseudomonas fluorescens (strains 1 and 2) and Bacillus subtilis on the growth and yield of onion and on the microorganisms in the rhizosphere of onion. The ability of microorganisms to produce indole-acetic acid (IAA), siderophores and to solubilize tricalcium phosphate (TCP) was also assessed. The experiment was conducted in field conditions, in chernozem type of soil. Bacillus subtilis was the best producer of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 22 publications
0
11
0
3
Order By: Relevance
“…Although previous studies reported the positive and negative effects of PGPB on onion (Allium cepa Linn.) (Jha et al, 2005;Čolo et al, 2014), few PGPB have been isolated from onion even though Taiwan ranks third in the world for onion yield hectare -1 (Fatih, 2018). Due to the low absorption and penetration abilities of the onion's root system as well as the high potential for weed invasion during planting, onion is a suitable candidate for the application of PGPB.…”
mentioning
confidence: 99%
“…Although previous studies reported the positive and negative effects of PGPB on onion (Allium cepa Linn.) (Jha et al, 2005;Čolo et al, 2014), few PGPB have been isolated from onion even though Taiwan ranks third in the world for onion yield hectare -1 (Fatih, 2018). Due to the low absorption and penetration abilities of the onion's root system as well as the high potential for weed invasion during planting, onion is a suitable candidate for the application of PGPB.…”
mentioning
confidence: 99%
“…Bacillus circulans CB7 isolated from apple rhizosphere soil with multifaceted PGP traits like P‐solubilization, production of auxins, ACC deaminase and siderophore was shown to have positive influence on the plant growth parameters in tomato under net house condition (Mehta et al ). Bacillus subtilis with the ability to produce IAA was shown to influence the plant growth and yield of onion (Čolo et al ). Bacillus velezensis FZB42, a model for plant growth promoting, and biocontrol strains of Bacillus have been shown to promote growth and suppress diseases in various crops like potato, cotton, wheat, tomato, strawberry and lettuce (Fan et al ).…”
Section: Bacillus and Plant Growth Promotion In Crop Plantsmentioning
confidence: 99%
“…Korelasi yang positif antara pertumbuhan vegetatif yang optimal dan peningkatan bobot umbi basah dan kering pada tanaman bawang merah yang diberi perlakuan kombinasi pupuk hayati dan pupuk kimia sintetik juga mengindikasikan bahwa mikrob pemacu pertumbuhan yang terkandung pada pupuk hayati mampu bersinergi dengan lingkungan tumbuh dan memberikan pengaruh terhadap peningkatan proses fisiologis tanaman dan akumulasi biomasa pada umbi bawang (Colo et al, 2014). Peningkatan kualitas pertumbuhan ini dimungkinkan berasal dari efek promotif pertumbuhan mikrob yang terkandung pada pupuk hayati dalam peningkatan penyerapan unsur hara akibat ketersediaan unsur hara yang meningkat dalam tanah (Nadeem et al, 2016;Yildirim et al, 2011) dan perlindungan tanaman terhadap serangan penyakit (Fernandes et al, 2018).…”
Section: Pengaruh Pupuk Hayati Terhadap Serangan Fusarium Pada Umbi Bunclassified